The Romantic Basis of a Poetic Ecology in Nerval's 'Vers dorés'. (2nd January 2020) - Mees, Martin
ABSTRACT: This article aims to follow in the footsteps of French ecocriticism, while creating a double shift in its point of view: firstly, by questioning the work of the romantic writer Gérard de Nerval, who has never truly been studied through the prism of ecopoetry. Secondly, by proposing a resolutely transdisciplinary analysis at the crossroads of literature and philosophy. This study highlights the modernity of Nerval's metaphysical conceptions of Nature but also how the poem 'Vers dorés' may become the manifesto of a poetic ecology through its performativity and its mobilisation of the figure of ruin.